Yamal on the edge: Arctic Environmental Governance in times of accelerated industrial development - French, Nadia (2023)
The changing landscape and economic relevance of the Arctic present a unique opportunity to monitor the change in interactions between people and the arctic nature as well as to shed light onto the top-down translation of the existing at different scales environmental governance regimes. The Russian Arctic Zone occupies over a third of the total area of the Arctic, yet no Arctic-specific legislation or environmental protection authority exists to oversee the so-called ‘resource base’ of the Russian state. The growing competition for the influence in the Russian Arctic zone of various actors (international Arctic fora, foreign investors and suppliers, hydrocarbon companies, government institutions) already brings issues of ecological impact to the fore, render them visible, and provide space for renegotiating institutional, normative and other conditions. Yet, little is known about how these developments reflect on environmental governance or socioecological relations in the remote corners of the Russian Arctic affected by the new lap of industrialisation. The insight into environmental governance in the Russian Arctic with a case study of the area of Russia’s flagman mega-project on Yamal peninsula, translated from Nenets as the ‘edge of the land’, may reveal the emerging mechanisms for environmental protection as well as ungovernable spaces in the ecologically and socioeconomically challenged area of the Far North. The work done within the framework of Lefebvre’s spatial trialectics superimposed onto the Russian Arctic attempted to understand and map the structure, scope and utility of environmental governance in the region and through socioecological lens to explore ground-scale interactions between human and non-human actants (individual and community-based behaviour that can impact the environment especially if ￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼ ￼multiplied) in a case study conducted in Mys Kamenny, Yamal district, Russia in 2017. Yamal peninsula is an area of rapid socioeconomic development undergoing noticeable ...